Efecto del bap y 2.4d en el establecimiento in vitro de láminas foliares y segmento nodales de moringa oleífera lam - Sánchez Benítez, Cristina Cumandá (2014)
In the laboratory of Biotechnology, Faculty of Agricultural Sciences At Universidad Tècnica Machala was investigated on the ability of invitro propagation of Moringa (Moringa Oleifera Lam, 2013) exotic species. The objectives were Three. Determine the best disinfection effect for planting and establishment of leaf blades and nodal segments using sodium hypochlorite at 2% and 7% absolute alcohol. April. Establish the best dose of BAP and 2-4D for training callogenico tissue explants, nodal segments and leaf blades. In research camera was used slice, autoclave, analytical balance, oven, stirrer, pH meter, water distiller, refrigerator, petris boxes, jars, bottles, test tubes, tweezers, scissors, lighter, knife and peseta; implants leaves and nodal segments of Moringa, aluminum foil, paper towels, parfilm, scalpels, ruler, markers, liquid antibacterial soap, alcohol, bleach, detergent and sterile distilled water (ADE). The eight treatments consisted of four dose of BAP and 2, 4-D (0.5, 0.75, 1.0, 1.25 mg / l 0.1. 0.25, 0.5 and 0.75 mg / l) and two kinds of foil sheets explants and nodal segments. The variables studied were: number of explants with callogenico tissue formation (TC) in leaf blades and nodal segments. Coverage area of tissue explants with callogenico nodal segments and leaf blades. And Percentage of contamination. The leaf blades consisted of longitudinal cuts leaves, 1cm2 containing a portion of the central vein. The leaf explants were placed in boxes with petris sterilized culture medium at five explants per box is sealed and located in hatching chambers. The nodal segments were inoculated in MS medium containing test tubes, one tube sealed and then placed in an incubation chamber. The experiment consists of eight treatments, which are divided into 4 treatments for nodal segments and 4 leaf blades with 10/15 repeats respectively, giving a total of 40/300 units. The design used was Completely Randomized with different number of replications per treatment in the laboratory was no difference in the percentage of contamination lamínales and nodal explants disinfection treatment to sodium hypochlorite 2% more absolute alcohol 7% NaClO. At 21 days the contamination came to 71% in lamellar explants and 41.1% in zero nodal segments. The nodal segments show a higher percentage of explants with callogenico tissue and explant callogenico coverage that included nominal scales advanced and profuse. The leaf blades have a lower percentage of explants and profuse in the advanced category. And medium and high levels of BAP and 2, 4-D stimulated the formation of callogenico tissue as assessed at 35 and 45 days.